The Relationship Between Self Efficacy And Self Care Practices In Stroke Patients At The Neurology Clinic Rsud Dr Mohamad Soewandhie Surabaya - Retno Wahyuningtyas; Nunik Purwanti; Nur Hidaayah; Siti Nur Hasina (Journal for Quality in Public Health, 2025)
Stroke is one of the leading causes of long-term disability that affects patients' ability to perform self-care. One important factor influencing self-care behavior is self-efficacy, which refers to an individual's belief in their capability to carry out self-care activities. High self-efficacy can enhance patient participation in the recovery process and improve quality of life. This study aims to examine the relationship between self-efficacy and self-care behavior among stroke patients at the Neurology Clinic of RSUD Dr. Mohamad Soewandhie Surabaya. The research method employed a cross-sectional approach. The study population consisted of 228 stroke patients at the Neurology Clinic of RSUD Dr. Mohamad Soewandhie Surabaya. A sample of 146 patients was selected using purposive sampling technique. The independent variable was self-efficacy, while the dependent variable was self-care behavior. Research instruments included the Stroke Self-Efficacy Questionnaire (SSEQ) to measure self-efficacy and the Barthel Index (BI) to assess self-care behavior. Data analysis was performed using the Chi-Square test with a significance level of <0.05. The results showed that the majority of respondents had high self-efficacy (80.8%) and good self-care behavior (79.5%). Statistical analysis revealed a significant relationship between self-efficacy and self-care behavior (p = 0.001). It can be concluded that there is a significant relationship between self-efficacy and self-care behavior among stroke patients at the Neurology Clinic of RSUD Dr. Mohamad Soewandhie Surabaya. This finding underscores the importance of enhancing self-efficacy to support stroke patients' recovery and independence.